Oxygen Exchange in Leaves in the Light - Canvin, David T. (1980)
Photosynthetic O(2) production and photorespiratory O(2) uptake were measured using isotopic techniques, in the C(3) species Hirschfeldia incana Lowe., Helianthus annuus L., and Phaseolus vulgaris L. At high CO(2) and normal O(2), O(2) production increased linearly with light intensity. At low O(2) or low CO(2), O(2) production was suppressed, indicating that increased concentrations of both O(2) and CO(2) can stimulate O(2) production. At the CO(2) compensation point, O(2) uptake equaled O(2) production over a wide range of O(2) concentrations. O(2) uptake increased with light intensity and O(2) concentration. At low light intensities, O(2) uptake was suppressed by increased CO(2) concentrations so that O(2) uptake at 1,000 microliters per liter CO(2) was 28 to 35% of the uptake at the CO(2) compensation point. At high light intensities, O(2) uptake was stimulated by low concentrations of CO(2) and suppressed by higher concentrations of CO(2). O(2) uptake at high light intensity and 1000 microliters per liter CO(2) was 75% or more of the rate of O(2) uptake at the compensation point. The response of O(2) uptake to light intensity extrapolated to zero in darkness, suggesting that O(2) uptake via dark respiration may be suppressed in the light. The response of O(2) uptake to O(2) concentration saturated at about 30% O(2) in high light and at a lower O(2) concentration in low light. O(2) uptake was also observed with the C(4) plant Amaranthus edulis; the rate of uptake at the CO(2) compensation point was 20% of that observed at the same light intensity with the C(3) species, and this rate was not influenced by the CO(2) concentration. The results are discussed and interpreted in terms of the ribulose-1,5-bisphosphate oxygenase reaction, the associated metabolism of the photorespiratory pathway, and direct photosynthetic reduction of O(2).